2013
DOI: 10.1111/ens.12050
|View full text |Cite
|
Sign up to set email alerts
|

Ecological characteristics of insects that affect symbiotic relationships with mites

Abstract: Parasites and pathogens that begin as symbionts, i.e., organisms living together in the same habitat, are some of the most promising drivers of species evolution. Because insects are highly diverse and important as ecosystem service agents and because mites can exert large effects on insect populations (capable of killing at least juveniles), insect-mite interactions have been analyzed from various perspectives, including evolutionary, ecological and pest-management perspectives. Here, I review and examine ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 104 publications
1
10
0
Order By: Relevance
“…Some mite species are mutualistic, offering ‘cleaning services’ to insects by reducing the pathogenic fungi community in their nests (Biani et al., ), or by consuming wastes. Additionally, some mites can promote the transmission and survival of fungi species that have a positive effect on insect fitness (Okabe, ). However, mites can reduce the reproductive success of insects by transferring parasitic fungi into the nest (Okabe, ), and they can also feed on eggs and larvae, or consume the larvae's food, thus hampering larval development (Cordeiro et al., ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some mite species are mutualistic, offering ‘cleaning services’ to insects by reducing the pathogenic fungi community in their nests (Biani et al., ), or by consuming wastes. Additionally, some mites can promote the transmission and survival of fungi species that have a positive effect on insect fitness (Okabe, ). However, mites can reduce the reproductive success of insects by transferring parasitic fungi into the nest (Okabe, ), and they can also feed on eggs and larvae, or consume the larvae's food, thus hampering larval development (Cordeiro et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, some mites can promote the transmission and survival of fungi species that have a positive effect on insect fitness (Okabe, ). However, mites can reduce the reproductive success of insects by transferring parasitic fungi into the nest (Okabe, ), and they can also feed on eggs and larvae, or consume the larvae's food, thus hampering larval development (Cordeiro et al., ). Previous analyses of interactions between Nicrophorus species and P. carabi suggests that the nature of the relationship between the mite and the beetle is similarly variable.…”
Section: Introductionmentioning
confidence: 99%
“…Symbionts can be found in the insect itself, for example in the gut or in specialized cells called bacteriocytes (Paniagua Voirol et al 2018). Some symbionts proliferate on the insect's exterior surface or in their habitat, such as their nest or food provisions (Okabe 2013;Kaltenpoth and Engl 2014;Hoang et al 2019). Not all microbes associated with insects or their environment, however, are involved in a symbiotic relationship.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Okabe and Makino (2008) clearly showed that the mite Ensliniella parasitica Vitzthum benefits its host, the wasp Allodynerus delphinalis (Giraud), by providing protection against parasitic wasps (Okabe and Makino 2008). However, in many other instances of specialized mite-insect associations, the way in which the presence of mites may benefit the insect has not been fully clarified (Lindquist 1975;Okabe 2013;Hofstetter and Moser 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Mites are often found in structures built by insects, for example those build by social insects, and these associations can be obligate or simply opportunistic (Eickwort 1990;Okabe 2013). Here we investigated the mite fauna associated with the egg masses of the viburnum leaf beetle Pyrrhalta viburni (Paykull) (Coleoptera: Chrysomelidae).…”
Section: Introductionmentioning
confidence: 99%